A simplified human head finite element model for brain injury assessment of blunt impacts - Mohd Hasnun Ariff, Hassan; Zahari, Taha; I., Hasanuddin; Anwar, P. P. Abdul Majeed; H., Mustafa; Nur Aqilah, Othman (Faculty Mechanical Engineering, UMP, 2020)
Blunt impacts contribute more than 95% of brain trauma injuries in Malaysia. Modelling and simulation of these impacts are essential in understanding the mechanics of the injuries to develop a protective equipment that might prevent brain trauma. Various finite element models of human head have been developed, ranging from two-dimensional models to very complex three-dimensional models. The aim of this study is to develop a simplified three-dimensional human head model with low computational cost, yet capable of producing reliable brain responses. The influence of different head-neck boundary conditions on the brain responses were also examined. Our model was validated against an experimental work on human cadaver. The model with free head-neck boundary condition was found to be in good agreement with experimental results. The head-neck joint was found to have a significant influence on the brain responses upon impact. Further investigations on the head-neck joint modelling are needed. Our simplified model was successfully validated against experimental data on human cadaver and could be used in simulating blunt impact scenarios.